Characteristics and mechanism of toluene removal by double dielectric barrier discharge combined with an Fe2O3/TiO2/γ-Al2O3 catalyst. Issue 68 (13th November 2020) - Wang, Rui; Ren, Jiaze; Wu, Jiangyou; Wu, Lanlan
Abstract : The removal efficiency of toluene and CO2 selectivity were improved and the production of O3 and NOx was reduced by using DBD combined with different catalysts. Abstract : Removal of volatile organic compounds (VOCs) by non-thermal plasma technology produced by dielectric barrier discharge has become a hotspot due to its rapid reaction at room temperature, convenience without preheating and high removal efficiency of VOCs. Ways to improve the removal efficiency of mixed VOCs and the control of by-products in the discharge process are urgently needed. In view of the above shortcomings, the research progress of catalysts to improve the removal efficiency of VOCs by dielectric barrier discharge in recent years was reviewed; in this research, we conducted experiments on the removal efficiency of toluene under high flow rate experimental conditions (input voltage 10–70 V, mixed gas flow rate 1 m 3 h −1, inlet concentration 1000 mg m −3 ). The research used γ-Al2 O3, TiO2 /γ-Al2 O3 and Fe2 O3 /TiO2 /γ-Al2 O3 as catalysts in a reactor with a discharge gap of 6 mm, and a 99.7% removal efficiency of toluene was achieved when the SIE was 183.4 J L −1 . The added catalyst significantly reduced the concentration of by-products. At the same time, experiments with multiple catalysts to improve the removal efficiency and the performance of the discharge effect under different humidity levels were analyzed. The removal efficiency of toluene was optimized and recyclable, the formation of by-products was effectively suppressed when the catalysts in the reactor were Fe2 O3 /TiO2 /γ-Al2 O3, TiO2 /γ-Al2 O3 and γ-Al2 O3, and the discharge length was 1 : 2 : 2.